PEMENUHAN KESEJAHTERAAN ANAK YANG ORANG TUANYA MENGALAMI PERCERAIAN (KASUS KELUARGA S DI KELURAHAN RAGUNAN, JAKARTA SELATAN): Legal Analysis Of The Fulfillment Of The Welfare Of Children Whose Parents Have Divorce (Case Of Family S In Ragunan Village, South Jakarta City) - Zelina Widad; Krestianto, Indra (Reformasi Hukum Trisakti, 2025)
Child welfare is a condition that ensures a child's physical, mental, and social growth and development. In the context of families that have experienced divorce, the fulfillment of child welfare tends to be disrupted, leaving children in a situation vulnerable to developmental obstacles. This study aims to examine child welfare after divorce based on Decision Number: 4388/Pdt.G/2019/PA.JS, and explore efforts that can be made to ensure that children continue to receive their rights properly. The method used is a socio-legal approach with a descriptive research nature. Primary data was obtained through interviews, while secondary data was collected through literature studies. The results of the study indicate that children who are victims of divorce, as stated in the decision, experience impaired growth and development that are not appropriate for their age. This is caused by minimal support from parents and the surrounding environment in ensuring the fulfillment of children's basic needs. These findings underscore the importance of the role of all elements of society in providing comprehensive protection and support for children from divorced families, to ensure they can continue to live decently and prosperously as mandated by laws and regulations.